Synthesis, characterization, PXRD studies, and theoretical calculation of the effect of gamma irradiation and antimicrobial studies on novel Pd(II), Cu(II), and Cu(I) complexes - Hassan, Safaa S.; Aly, Samar A.; Al-Sulami, Ahlam I.; Albohy, Salwa A. H.; Salem, Mohamed F.; Nasr, Ghada M.; Abdalla, Ehab M. (Frontiers in Chemistry, 2024)
The main objective of this study is to synthesize and characterize of a new three complexes of Pd (II), Cu (II), and Cu (I) metal ions with novel ligand ((Z)-2-(phenylamino)-N'-(thiophen-2-ylmethylene)acetohydrazide) H2LB. The structural composition of new compounds was assessed using several analytical techniques including FT-IR, 1H-NMR, electronic spectra, powder X-ray diffraction, and thermal behavior analysis. The Gaussian09 program employed the Density Functional Theory (DFT) approach to optimize the geometry of all synthesized compounds, therefore obtaining the most favorable structures and crucial parameters. An investigation was conducted to examine the impact of γ-irradiation on ligands and complexes. Before and after γ-irradiation, the antimicrobial efficiency was investigated for the activity of ligands and their chelates. The Cu(I) complex demonstrated enhanced antibacterial activity after irradiation, as well as other standard medications such as ampicillin and gentamicin. Similarly, the Cu(I) complex exhibited superior activity against antifungal species relative to the standard drug Nystatin. The docking investigation utilized the target location of the topoisomerase enzyme (2xct) chain A.